0915 The Effects of Eszopiclone on Spindles, Slow Oscillations and their Coordination in Health and Schizophrenia. (12th April 2019) - Mylonas, Dimitris; Demanuele, Charmaine; Baran, Bengi; Cox, Roy; Stickgold, Robert; Manoach, Dara S
Abstract: Introduction: Patients with schizophrenia have sleep spindle deficits that correlate with impaired sleep-dependent memory consolidation. In a previous study of schizophrenia, eszopiclone, a non-benzodiazepine sedative hypnotic, despite increasing spindles, failed to improve memory. Here, we investigated whether this failure reflected that eszopiclone disrupts slow oscillations (SOs) and their coordination with spindles, both of which are critical for memory consolidation. Methods: Twenty-six chronic, medicated patients with schizophrenia (32±8yrs, 21 male) and 29 demographically matched healthy controls participated in a double-blind, placebo-controlled, cross-over study. Placebo and eszopiclone visits both involved polysomnography on two consecutive nights. On the second night of each visit, participants trained on the finger tapping motor sequence task (MST) and were tested the following morning. We evaluated eszopiclone effects on SOs (0.5-4Hz), spindles (12-15Hz), SO phase at spindle peak (timing) and the variability of this timing (consistency) during stage 2 non-rapid eye movement sleep and how they related to overnight improvement of MST performance. Results: Regardless of group and condition (eszopiclone, placebo), SO-spindle coordination, both timing and consistency, were stable across nights. While timing did not differ between groups, patients unexpectedly were more consistent (pcorrected =.01). Eszopiclone affected both groups similarly: it increased spindle density (pcorrected <.001), reduced the consistency of SO-spindle timing (pcorrected <.001) and reduced SO amplitude (pcorrected <.001). Eszopiclone did not improve memory (p=.16). At the placebo visit, spindle density correlated with overnight MST improvement (pcorrected =.05). At the eszopiclone visit, SO amplitude, but not spindle density (pcorrected =.19), predicted overnight MST improvement and only in schizophrenia (Amplitude by Group interaction pcorrected =.04; Schizophrenia, r=.44, p=.03). Conclusion: Eszopiclone changed the morphology of SOs, made their timing in relation to spindles less consistent and not only did not improve memory, but disrupted the correlation between overnight improvement's and spindle density. This suggests that interventions to improve memory need not only to increase spindle density but also to preserve or enhance both SOs and their coordination with spindles. Support (If Any): This research was supported by 1R01MH092638 (DSM, RS), R01MH08832 (RS), and Vergottis Fellowship (DM).